Adolescents' sociosexual orientation is related to attachment to their same-sex parent. (1st May 2018) - Mallet, Pascal; Kindelberger, Cécile
Abstract: We set out to show that sociosexual orientation (SSO) and erotophilia are two different traits that can be evidenced as early as middle adolescence, and to examine their associations with attachment to parents. Self-report scales measuring SSO, erotophilia, and attachment to the mother and the father were administered to 289 12- to 17-year-olds. Based on an exploratory factor analysis, SSO and erotophilia are two different, consistent dimensions in this age range. A six-month test-retest revealed a moderate-to-high rank-order stability of the two traits, which were positively and moderately correlated. Boys scored higher than girls on both traits. During the six-month interval between T1 and T2, erotophilia increased whereas SSO did not change. Regression analyses showed that a positive perception of attachment to the same-sex parent among boys accounted for SSO, regardless of perceived attachment to the other-sex parent. This held true for girls also, but to a lesser extent. In the discussion, we emphasize the differences between boys' and girls' mating behavior, and the differences between attachment to same-sex vs other-sex parents as possible influences on SSO. Highlights: Sociosexuality and erotophilia are two consistent traits of teenagers. Their rank-order stability suggests that they are affected by individual experiences. Boys score higher than girls on unrestricted sociosexuality and erotophilia. Erotophilia increases with age, whereas sociosexuality does not. Specific attachment to the same-sex parent predicts adolescent sociosexuality.